Gastrointestinal Endoparasite Infection on Red Foot (Chelonoidis carbonaria) in Surabaya City Based on Fecal Examination - Nurin Ardhiani; Endang Suprihati; Aditya Yudhana; Faisal Fikri (Universitas Airlangga, 2021)
Infectious disease which caused by parasite is the most serious problem in tortoise breeding. This study identifies gastrointestinal endoparasites infection on Red Foot (Chelonoidis carbonaria) during November 2020 to February 2021 in Surabaya City. Fecal samples from a tortoise, a total of 14 tortoises were collected and examined by native, sedimentation and floatation methods for parasitic eggs and oocyst. Fecal samples for this research were collected from breeding farm in Surabaya City. Data obtained from this study were presented descriptively and analyzed by Chi-Square test. Based on examination results, the occurrence of gastrointestinal endoparasite infection on Red foot was recorded at 100% from the total samples. The gastrointestinal parasites were identified as helminths and protozoa namely which is dominately by Tachygonetria spp. (14%), Angusticaecum spp. (3%), and Balantidium coli (2%) respectively. The provision of deworming medication as a curative measure by the owner is carried out regularly and continuously on tortoises that are positively infected with gastrointestinal endoparasites and prevention can be done by paying attention to the management and cleanliness of the cage to prevent potential transmission of endoparasites from the environment to the tortoise.